EFEK PROGRAM PISA TERHADAP KURIKULUM DI INDONESIA - Indah Pratiwi (Jurnal Pendidikan dan Kebudayaan, 2019)
This paper discusses how PISA score affects the curriculum in Indonesia. Since participating in PISA in 2000, Indonesia continuously ranks in the lower level. In 2015, Indonesia ranked 65 from 69 participantsâ€™ countries. This affects to Indonesiaâ€™s image in the eyes of international world as it was considered that Indonesia had not succeeded to provide quality education by using international standards. The aim of this paper is to examine how public and international pressures affect the education policy in Indonesia. The method used in collecting data was by utilizing secondary data and compiling news from national media. The news compilation was analyzed using discourse analysis to depict the public pressure to change the curriculum in Indonesia. The discourse analysis focused on three mainstream newspapers in Indonesia, which used PISA score as headlines. The analysis was to examine the public response toward PISA score and public opinions regarding the on going education process. To support the analysis, this study also examined documents released by the ministry of education and culture to find out the direction of education policy in Indonesia which was set according to instruments used in PISA. The study was conducted with a study desk for six months. The results found that curriculum changes in Indonesia is very inline with PISA. One of the reasons is the existence of public pressure through capable mass media and the crackdown given in PISA which is considered capable of describing the quality of Indonesian education as a whole. It is conluded that curriculum changes in Indonesia is considered the impact of the PISA program.AbstrakArtikel ini mengkaji pengaruh capaian PISA terhadap kurikulum di Indonesia. Sejak bergabung menjadi partisipan PISA pada tahun 2000 capaian indeks Indonesia secara konstan selalu berada pada level bawah dalam indeks PISA. Terbukti pada tahun 2015 Indonesia menempati urutan ke 65 dari 69 negara partisipan PISA. Di mata masyarakat dan lingkungan internasional Indonesia dianggap belum berhasil dalam menyelenggarakan pendidikan dengan standar internasional. Tujuan penulisan artikel ini adalah untuk melihat bagaimana PISA memengaruhi kebijakan pendidikan di Indonesia. Metode yang digunakan adalah data sekunder dan kumpulan berita dari sejumlah media nasional. Berita dari sejumlah media akan digunakan sebagai analisis wacana yang menunjukkan adanya tekanan publik untuk mengubah kurikulum di Indonesia. Analisis wacana ini diambil dari tiga koran di Indonesia yang menjadikan hasil PISA sebagai berita utama. Hal ini dianalisis untuk melihat bagaimana respon publik menilai hasil PISA dan opini publik terhadap proses pendidikan yang selama ini berjalan. Untuk menguatkan analisis tersebut kajian ini menggunakan dokumen dari Kementerian Pendidikan dan Kebudayaan untuk melihat arah kebijakan pendidikan di Indonesia yang dirancang sesuai dengan tools PISA. Penelitian dilakukan dengan desk studi selama enam bulan. Hasil yang ditemukan adalah bahwa perubahan kurikulum di Indonesia sangat sejalan dengan PISA. Salah satu penyebabnya adalah adanya tekanan publik melalui media massa terhadap peringkat yang diberikan dalam PISA yang dianggap mampu menggambarkan kualitas pendidikan Indonesia secara keseluruhan. Maka simpulan dalam artikel ini adalah perubahan kurikulum di Indonesia merupakan dampak dari program PISA.Â